Differential Role of Psychosocial, Health Care System and Neighborhood Factors on the Retention in HIV Care of Women and Men in the Ryan White Program. (19th August 2020) - Trepka, Mary Jo; Sheehan, Diana M.; Dawit, Rahel; Li, Tan; Fennie, Kristopher P.; Gebrezgi, Merhawi T.; Brock, Petra; Beach, Mary Catherine; Ladner, Robert A.
We investigated potential differential impact of barriers to HIV care retention among women relative to men. Client intake, health assessment, service, and laboratory information among clients receiving medical case management during 2017 in the Miami-Dade County Ryan White Program (RWP) were obtained and linked to American Community Survey data by ZIP code. Cross-classified multilevel logistic regression analysis was conducted. Among 1609 women and 5330 men, 84.6% and 83.7% were retained in care. While simultaneously controlling for all demographic characteristics, vulnerable/enabling factors, and neighborhood indices in the model, younger age, being US born, not working, and having a medical provider with low volume (<10) of clients remained associated with non-retention in care among women and men; while having ≥3 minors in the household and being perinatally infected were additionally associated with retention only for women. Both gender-specific and gender-non-specific barriers should be considered in efforts to achieve higher retention rates.